New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea - Blake, James A. (Zootaxa, 2020)
Eighteen species of Orbiniidae, 15 new to science, are reported from deep-sea habitats in the Pacific Ocean and the South China Sea. The collection includes specimens from continental slope and abyssal soft sediments as well as hydrothermal vent and methane seep sites. New collections of Califia calida Hartman, 1957, Naineris uncinata Hartman, 1957, and Phylo nudus (Moore, 1911) allow redescription and new distributional records of these species to be documented. Five species of Leitoscoloplos: L., cliffordi n. sp., L. gordaensis n sp., L. lunulus n. sp., L. sahlingi n. sp., and L. williamsae n. sp. are described together with a new species of Berkeleyia, B. lelievre n. sp., two new species of Scoloplos: S. californiensis n. sp. and S. sparsaciculus n. sp., and a new species of Leodamas, L. bathyalis n. sp. In addition, six new species of Orbiniella are described: O. abyssalis n. sp., O. eugeneruffi n. sp., O. grasslei n. sp., O. longilobata n. sp., O. rugosa n. sp., and O. tumida n. sp.